UPAYA MENINGKATKAN AKHLAK TERPUJI SISWA MELALUI PEMBIASAAN DI LINGKUNGAN SEKOLAH SMK 2 NEGERI SUKABUMI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze efforts to improve students’ noble character through habituation in the school environment of SMK Negeri 2 Sukabumi. The background of this research is based on the importance of character building, which not only focuses on cognitive aspects but also emphasizes moral development as a fundamental goal of national and Islamic education. This study employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation involving the principal, teachers, and students as research subjects. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that habituation serves as a primary strategy in improving students’ noble character. The forms of habituation are implemented through daily, weekly, and incidental activities that incorporate values such as discipline, responsibility, honesty, politeness, and social awareness. The strategies applied include consistent implementation, teacher role modeling, a humanistic approach, and active student involvement in various activities. Continuous habituation has been proven to positively influence students’ behavior, although the level of improvement varies depending on students’ participation. The study also identifies supporting factors such as a conducive school environment and strong teacher commitment, as well as inhibiting factors including external environmental influences and low student awareness. Therefore, continuous efforts are needed through program innovation and collaboration between schools and parents. In conclusion, habituation can be an effective method in fostering students’ noble character comprehensively.